Kewajiban Anak Menafkahi Orang Tua (Studi Perbandingan KHI Dan KUH Perdata) - Fitriani; Hartono; Achmad Fahruddin (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Child maintenance to parents has been regulated in Islamic law and positive law. But in reality there are still many who neglect these orders. So this study aims to discuss how the review of Islamic law and civil law as well as the similarities and differences regarding child maintenance to parents. This research uses the library research method by collecting and analyzing secondary data. The main data source includes the obligation of children to parents in providing maintenance comparing the compilation of Islamic law and civil law. The results showed that 1) the obligation of children to provide for parents in the perspective of Islamic law which includes filial piety to parents in Islam includes providing maintenance if parents are in an incapable condition. 2) The obligation of children to support parents in civil law is supported by the Civil Law Act. 3) A comparison between Islamic law and civil law on the obligations of children to parents looks at the differences and similarities of positive law and civil law.